2019
DOI: 10.1101/726190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered theta / beta frequency synchrony links abnormal anxiety-related behavior to synaptic inhibition in Neuroligin-2 knockout mice

Abstract: Inhibitory synaptic transmission plays a key role in the circuits underlying anxiety behaviors, but the network mechanisms by which disruptions in synaptic inhibition contribute to pathological anxiety processing remain largely unknown. Here we addressed this question in mice lacking the inhibitory synapse-specific adhesion protein Neuroligin-2 (Nlgn2), which display widespread reduction in inhibitory synaptic transmission as well as a pronounced anxiety phenotype. To investigate how the lack of synaptic inhib… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
(118 reference statements)
1
4
0
1
Order By: Relevance
“…In particular, constitutive deletion of NLGN2 resulted in an exag gerated activation of the BLA and its projections to the CeA under aversive conditions, consistent with the notion that the reduced synaptic inhibition results in neuronal overactivation in key regions mediating affective behaviors (45,46). Accordingly, local Cremediated deletion of NLGN2 from the BLA recapitulated some (but not all) aspects of the anxiety phenotype of the constitutive Nlgn2 KO mouse (80). Similarly, loss of NLGN2 from the ventral hippocampus (vHPC), another key region in the anxiety circuitry, resulted in an increase in freezing behaviors under specific anxiogenic conditions (80).…”
Section: Nlgn2 In Anxiety-like Defensive Behaviorssupporting
confidence: 77%
See 3 more Smart Citations
“…In particular, constitutive deletion of NLGN2 resulted in an exag gerated activation of the BLA and its projections to the CeA under aversive conditions, consistent with the notion that the reduced synaptic inhibition results in neuronal overactivation in key regions mediating affective behaviors (45,46). Accordingly, local Cremediated deletion of NLGN2 from the BLA recapitulated some (but not all) aspects of the anxiety phenotype of the constitutive Nlgn2 KO mouse (80). Similarly, loss of NLGN2 from the ventral hippocampus (vHPC), another key region in the anxiety circuitry, resulted in an increase in freezing behaviors under specific anxiogenic conditions (80).…”
Section: Nlgn2 In Anxiety-like Defensive Behaviorssupporting
confidence: 77%
“…Accordingly, local Cremediated deletion of NLGN2 from the BLA recapitulated some (but not all) aspects of the anxiety phenotype of the constitutive Nlgn2 KO mouse (80). Similarly, loss of NLGN2 from the ventral hippocampus (vHPC), another key region in the anxiety circuitry, resulted in an increase in freezing behaviors under specific anxiogenic conditions (80). In contrast, local deletion of Nlgn2 from the mPFC (48) or the LS (49) led to a pronounced reduction in anxietylike behaviors, likely re flecting a loss of inhibition onto anxiolytic projections from the mPFC to subcortical structures (48) or from the LS to the lateral hypothalamus (49).…”
Section: Nlgn2 In Anxiety-like Defensive Behaviorsmentioning
confidence: 88%
See 2 more Smart Citations
“…In rodents, changes in slow hippocampal gamma rhythms are generally associated, among other things, with slower running speed or increase in synchronization between CA3 and the cingulate cortex during immobility (Ahmed and Mehta, 2012;Buzsáki, 1986;Buzsáki and Wang, 2012;Zheng et al, 2015). Other studies showed that alteration gamma with anxiety behaviors (Batashvili et al, 2019;Cruces-Solis et al, 2019;Zhou et al, 2018). Nevertheless, to our knowledge, there is no study showing a systematic effect of aging on magnitude of gamma power, except when degeneration is present (Etter et al, 2019;Goutagny et al, 2013).…”
Section: Discussionmentioning
confidence: 85%